Assessing the applicability of Emiliania huxleyi coccolith morphology as a sea‐surface salinity proxy - Samuel R. Fielding; Jens O. Herrle; Jórg Bollmann; Richard H. Worden; David J. S. Montagnesd (Limnology and Oceanography, 2009)
Culture experiments were used to assess the applicability of Emiliania huxleyi coccolith morphology as a palaeo‐sea‐surface salinity (SSS) proxy. Coccolith morphology was dependent on salinity over a range reflecting present day marine conditions; both coccolith size and the number of coccolith elements increased linearly with increasing salinity. Using regression analysis, the effect of salinity on coccolith morphology was compared to those previously observed in sediment core‐top and plankton data. No significant differences were found between the slopes of these data, suggesting that salinity is the primary control on E. huxleyi coccolith size and element number in the ocean. However, the intercepts of the culture data were significantly higher. A combination of experimental and literature analysis indicated that temperature and nutrients were unlikely to be the causes of this discrepancy. Literature analysis also highlighted that coccolith size data from marginal environments displayed different intercepts to those from the open‐ocean data. This suggests that discrete morphotypes exist in these marginal locations. We, therefore, recommend that the original E. huxleyi coccolith morphology palaeo‐SSS transfer function requires further evaluation before being routinely applied.

Distribution, growth, diet and foraging behaviour of the yellow‐fin notothen Patagonotothen guntheri (Norman) on the Shag Rocks shelf (Southern Ocean) - M. A. Collins; R. S. Shreeve; S. Fielding; M. H. Thurston (Journal of Fish Biology, 2008)
The distribution, total length ( L T ) frequency and diet of Patagonotothen guntheri are described from 14 bottom trawl surveys conducted on the Shag Rocks and South Georgia shelves in the austral summers from 1986 to 2006. Patagonotothen guntheri (80–265 mm L T ) were caught on the Shag Rocks shelf from depths of 111 to 470 m, but no specimens were caught on the South Georgia shelf. Multiple cohorts were present during each survey and L T ‐frequency analysis of these cohorts suggests that growth was slow (von Bertalanffy K = 0·133). Evidence from stomach contents and acoustic data (2005 and 2006) showed that P. guntheri is primarily a pelagic feeder, migrating from the sea floor towards the surface to feed during daylight. The diet of smaller fish ( Rhincalanus gigas , whilst larger fish principally consumed the pelagic hyperiid amphipod, Themisto gaudichaudii and Antarctic krill Euphausia superba . Some larger fish also took benthic prey.

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)